Analisis Penerapan Bagi Hasil Dalam Sistem Paro Pada Masyarakat Peternak Sapi di Kabupaten Asahan - Agiet Mutiara Rengganis; Marliyah Marliyah; Wahyu Syarvina (Jurnal Ilmiah Ekonomi Islam, 2023)
Animal husbandry is one of the important sectors that builds the economy of cattle farmers in Asahan Regency. In addition, it is relatively easy to maintain. However, not all people are able to raise cattle due to the lack of capital to buy cows and limited time to manage pet cows. This condition has led to the emergence of a profit-sharing system in Asahan Regency. The purpose of this research is to analyse the implementation of the profit-sharing system in Asahan Regency. The research method used is descriptive qualitative. The results of the study explain that the profit sharing of the paro system in Asahan Regency is carried out with the agreement of both parties with the aim of mutual benefit and in its application is able to help the community's income. The paro system with 50:50 profit sharing is able to boost people's income in fulfilling their daily needs. Although this system is very beneficial for both capital owners and cattle farmers, there are often discrepancies in the profit-sharing contract that lead to misunderstandings. Therefore, it is necessary to improve and supervise the profit sharing system in Asahan Regency in order to establish good cooperation between capital owners and cattle farmers.